2019
DOI: 10.1161/jaha.118.011536
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatment Modality on Vascular Function in Coarctation of the Aorta: The LOVE‐COARCT Study

Abstract: Background Optimally treated patients with coarctation of the aorta remain at risk for late vascular dysfunction. The effect of treatment modality on vascular function is unknown. The LOVE‐COARCT (Long‐term Outcomes and Vascular Evaluation After Successful Coarctation of the Aorta Treatment) study was done to compare vascular function in patients with coarctation of the aorta treated with surgery, balloon dilation (BD), or stent implantation. Methods and Results In trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 64 publications
2
32
0
3
Order By: Relevance
“…CMR studies after surgical CoA repair showed that even normotensive patients have an increased aortic stiffness and that this is associated with increased LV mass [8, 25, 28]. Our results are comparable with a recently published study which did not show significant differences for aortic stiffness parameters between CoA who were either treated with surgery, balloon dilatation or stent implantation [11]. Babu-Narayan et al, however, showed that adult patients after endovascular stenting have an increased aortic distensibility and they also showed reduced blood pressure indices, improved LVEF and reduced LV mass index [10].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…CMR studies after surgical CoA repair showed that even normotensive patients have an increased aortic stiffness and that this is associated with increased LV mass [8, 25, 28]. Our results are comparable with a recently published study which did not show significant differences for aortic stiffness parameters between CoA who were either treated with surgery, balloon dilatation or stent implantation [11]. Babu-Narayan et al, however, showed that adult patients after endovascular stenting have an increased aortic distensibility and they also showed reduced blood pressure indices, improved LVEF and reduced LV mass index [10].…”
Section: Discussionsupporting
confidence: 84%
“…Babu-Narayan et al has shown improved aortic distensibility after stenting [10]. Another recent study found no difference in aortic stiffness and endothelial function between CoA patients who were treated with surgery, balloon dilation, or stent implantation [11].…”
Section: Introductionmentioning
confidence: 99%
“…885 A resposta da PA ao tratamento intervencionista depende da duração da HA antes da cirurgia e da idade do paciente. 886 Embora muitos reduzam a PA após o procedimento invasivo, uma grande proporção desenvolve HA exercício induzida. Os medicamentos anti-hipertensivos de escolha tanto para o periodo pré-operatório quanto para a PA residual após a cirurgia são os betabloqueadores (BB) e os inibidores da enzima conversora de angiotensina (IECA) ou o bloqueador do receptor AT1 da angiotensina II (BRA).…”
Section: Coarctação Da Aortaunclassified
“…The remaining full texts were requested via our library, but only 4 published in English were used. After consulting the full content of these 356 articles, only 17 fulfilled the inclusion criteria as set out above (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (Table 1).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%